An Objective Structured Clinical Examination to Assess Pharmacy Resident Performance - Kimberly A.B. Cauthon; Rebecca L. Attridge; Elizabeth M. Urteaga; Amy P. Witte (University of Minnesota Libraries Publishing, 2017)
Objective: The objective was to utilize an Objective Structured Clinical Examination (OSCE) for assessment of pharmacy residents. Innovation: Post-graduate year 1 (PGY1) and post-graduate year 2 (PGY2) pharmacy residents completing multiple, local residency programs were invited to participate in an OSCE. A total of eight PGY1 residents and one PGY2 resident completed the OSCE. American Society of Health-System Pharmacists (ASHP) residency program goals were aligned for each case, which were originally developed for a fourth-year pharmacy student OSCE. Station design included outpatient and inpatient settings with patient and physician interactions. Median communication and clinical skills scores were evaluated. Critical Analysis: The OSCE allows for assessment of all residents on common scenarios. Pharmacy residents met competency requirements and demonstrated excellent communication skills. The OSCE was able to evaluate both physician-pharmacist communication and patient-pharmacist communication. Baseline performance related to the ASHP goals and objectives was not completed; however, the OSCE could highlight resident strengths and weaknesses in communication and clinical skills. The OSCE could simulate independent practice, may reduce bias, and could provide an evaluation of the resident by a patient. However, the OSCE incurs higher resource utilization, specifically monetary and time, than other assessment methods. Next Steps: The pilot study results provide a beginning for further study of OSCEs for pharmacy residents. Further study should include surveying the residency directors about use of the OSCE, a comparison of performance between the OSCE and preceptor evaluations of residents on ASHP goals and objectives, and an evaluation of OSCE implementation at different time points within the residency. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties   Type: Note